The Influence of Applying the GASING Method on the Addition Skills of Third-Grade Elementary School Students in Batauga District, South Buton Regency - La Ode Maharudin; Wahyudin Wahyudin; Rina Heryani (Journal of Educational Sciences, 2026)
This study discusses the low addition skills of elementary school students by comparing the effectiveness of the GASING (Easy, Fun, Enjoyable) method and direct instruction. The aim is to analyze the influence of the GASING method on the addition skills of third-grade students. A quasi-experimental design was used with 45 students from two elementary schools in Batauga District, divided into experimental (n=23) and control (n=23) groups. Data was collected thru written tests administered as pretests and posttests. The results show that both methods significantly improved students' abilities with a very large effect size (Cohen's d > 3.5). However, the experimental group using the GASING method showed a significantly higher improvement, achieving a post-test average score of 92.23 (N-Gain = 0.90) compared to the control group using direct instruction with an average score of 80.00 (N-Gain = 0.73). This study concludes that the GASING method, which emphasizes learning thru concrete-representational-abstract development and mental calculation in an easy and fun way, is more effective than direct instruction in improving elementary school students' addition skills.